Dispersion of torsional waves in initially stressed multilayered circular cylinders - Cilli, A.; Ozturk, A. (SPRINGER, 2010)
Within the framework of a piecewise homogeneous body model, with the use of the three-dimensional linearized theory of elastic waves in initially stressed bodies, the propagation of torsional waves in prestressed multilayered circular cylinders is investigated. The elasticity relations for cylinder components are given through the Murnaghan potential. The influence of variations in the geometric and mechanical parameters of the cylinders on the dispersion curves is analyzed.
Keywords: propagation of torsional waves; initial stress; Murnaghan potential; multilayered cylinder; 3RD-ORDER ELASTIC-CONSTANTS; PROPAGATION; FIELD; SLAB; Mechanics; Materials Science; Polymer Science